Changing Fertility and Heterogeneous Motherhood Effects: Revisiting the Effects of a Parental Benefits Reform - Bernd Fitzenberger; Arnim Seidlitz (Institute of Labor Economics (IZA), 2024)
Using a semiparametric event study approach with a control group, we estimate the effect of motherhood on labor market outcomes in Germany, the child penalty. We further investigate how the 2007 parental benefits reform changed the child penalty while accounting for fertility effects. A large novel data set linking data from two administrative sources provides information on all births. Our estimation approach accounts for motherhood being a staggered treatment. The reform has small positive medium-run effects employment outcomes. It changes the selection into fertility and shows heterogeneous effects. However, the reform did little to reduce the average child penalty.
Keywords: J08; J13; J16; J22; 330; parental benefit reform; child penalty; semiparametric event study approach